Nonlinear models to describe the growth of Jatropha plant (Jatropha curcas L.) (Revista Ciência Agronômica, 2021)
Brazil stands out in the renewable energy sector due to the growing demand for clean energy sources, mainly withbiodiesel production, which uses vegetable oils and animal fats as raw material. With this, research has been developed with oilseedplants for this purpose and, among these plants, Jatropha has stood out for its productivity and ability to grow in regions with waterscarcity. Thus, it is necessary to study the growth of this plant over time to assist management techniques and detection of factors thataffect the plant development. Therefore, modeling this type of growth can subsidize knowledge and application of effi cient techniquesfor agricultural practices. The objective of this study was to fi t and compare the nonlinear Logistic and Gompertz models with fourparameters in the description of growth in height of the Jatropha plant according to days after the phenological cycle in the secondyear of the plant development, totaling 25 observations. The models were fi t using the statistical software R, considering the fi rstorder autoregressive error structure for the CNPAE-169 and CNPAE-259 accessions. All models fi t well to the data from the threeaccessions under study, but the Logistic model stood out for the CNPAE-169 and CNPAE-102 accessions and the Gompertz model forthe CNPAE-259 accession. The CNPAE-102 accession stood out from the others, presenting greater height in the study period.